2011
DOI: 10.5293/ijfms.2011.4.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Analysis of Impeller-Volute Interaction in Centrifugal Pump

Abstract: An unsteady numerical analysis has been carried out to study the strong impeller volute interaction of a centrifugal pump with six backward swept blades shrouded impeller. The numerical analysis is done by solving the threedimensional Reynolds Averaged Navier-Stokes codes with standard k-ε two-equations turbulence model and wall regions are modeled with a scalable log-law wall function. The flow within the impeller passage is very smooth and following the curvature of the blade in stream-wise direction. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The numerical predicted efficiency is higher than the experimental one by around 5%, because the mechanical and volumetric losses were not taken into account. Similar results with approximately the same computational mesh quality were presented in reference [10].…”
Section: Fig 10 Inlet Recirculation Vortex At Vertical Cross Sectionsupporting
confidence: 82%
See 1 more Smart Citation
“…The numerical predicted efficiency is higher than the experimental one by around 5%, because the mechanical and volumetric losses were not taken into account. Similar results with approximately the same computational mesh quality were presented in reference [10].…”
Section: Fig 10 Inlet Recirculation Vortex At Vertical Cross Sectionsupporting
confidence: 82%
“…The quality of the computational grid is an important condition for accurate numerical flow analysis results, particularly in the case of dominant decelerating flow in the pump [10,11]. Grid refinement is very important near the impeller walls.…”
Section: Design Of New Geometry Using Cfd Analysismentioning
confidence: 99%
“…This special model has proved that it is very helpful for our study because we do not have to use more accurate models that requires higher mesh accuracy such as y+ to be lower than 1. According to [6], they used different kinds of turbulence models and they found that the results did not change greatly. So, we directly used standard k-ε model specially [2] used it and the results were pretty good.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…The results showed that increasing the gap by this technique reduces the vibrations without affecting the performance badly but it was shown that this method is more effective at flow rates higher than the design flow rate or equal to it. Kean Wee Cheah, Thong See Lee and Sonny H. Winoto [6] carried out unsteady analysis of impeller-volute interaction in centrifugal pump. They used k-e model in FLUENT CFD package.…”
Section: Introductionmentioning
confidence: 99%
“…The unsteadiness of the pressure field increased as the volume flow was further removed from the best efficiency point. The unsteady velocity field resulting from the strong interactions of impeller/volute in a centrifugal pump was studied numerically by Cheah et al 2 A strong impeller/volute tongue interaction is observed near the volute tongue region based on the periodic fluctuations of pressure at the impeller outlet. These periodic pressure fluctuations at the impeller outlet were attributed to the change in position of the impeller blade relative to the tongue.…”
Section: Introductionmentioning
confidence: 99%